The Potential of Immersive Virtual Reality for the Study of Event Perception - Misersky, Julia; Peeters, David; Flecken, Monique (Frontiers in Virtual Reality, 2022)
In everyday life, we actively engage in different activities from a first-person perspective. However, experimental psychological research in the field of event perception is often limited to relatively passive, third-person computer-based paradigms. In the present study, we tested the feasibility of using immersive virtual reality in combination with eye tracking on participants in active motion. Behavioral research has shown that speakers of aspectual and non-aspectual languages attend to goals (endpoints) in motion events differently, with speakers of non-aspectual languages showing relatively more attention to goals (endpoint bias). In the current study, native speakers of German (non-aspectual) and English (aspectual) walked on a treadmill across 3-D terrains in VR, while their eye gaze was continuously tracked. Participants encountered landmark objects on the side of the road, and potential endpoint objects at the end of it. Using growth curve analysis to analyze fixation patterns over time, we found no differences in eye gaze behavior between German and English speakers. This absence of cross-linguistic differences was also observed in behavioral tasks with the same participants. Methodologically, based on the quality of the data, we conclude that our dynamic eye-tracking setup can be reliably used to study what people look at while moving through rich and dynamic environments that resemble the real world.